Modality of volition of a complex sentence in synchrony - Tuhai, O. (Studia Philologica, 2021)
The proposed article reveals the modality of volition of a complex sentence in the historical development of the English language in synchrony, namely in the Early New English language. The modality of a complex sentence is defined as a functional-semantic category with the relationship of the statement content to reality taking into account the predicative features of the category of time and volitional modality as the realization of an event or a situation. The syntactic category of the modality of volition is fixed in the paradigm of modus-dictum relationships with the emphasis on modus predicates to fix the fact of the actual speech situation and the expression of the addresser’s proposal. The communicative purpose of the modality of volition of a complex sentence is outlined in terms of the speaker’s attitude to the propositional or dictum basis of the statement content. The categories of subjective and objective modalities in a complex sentence of volitional semantics of the Early New English language are distinguished. Subjective modality is defined as the volitional modality in the main clause of a sentence with differentiation on voluntary and optative modalities with the meanings of the addresser’s will manifestation of order, command, desire, request, intention etc. Objective modality is determined as the propositional modality in a subordinate finite or infinitive predicative clause as the realization of a sentence proposition. The modal-pragmatic perspective of a complex sentence with the finite and infinitive predication of verbs of volition is outlined. The subjective volitional (voluntary and optative) modality is established to be realized in the modus modal-pragmatic framework while the objective propositional modality is explicated in the dictum modal-pragmatic framework of the studied sentence. The realization of subjective-objective modal relationships in an Early New English complex sentence is analyzed. Voluntary modal relationships are proved to be expressed in the paradigm «voluntary modus – propositional dictum» whereas optative modal relationships are actualized in the paradigm «optative modus – propositional dictum». The realization of voluntary and optative modalities of addresser’s will manifestation and the modal-temporal paradigm of the situation actualization is witnessed in the studied sentences-statements. The voluntary modality defines the modal relationships as «actual (potential) – real / real (unreal)» to denote the actual / potential real or the unreal situation. The modal relationships of the optative modality are established as «actual (potential) – unreal (real) / unreal» to denote the actual / potential unreal or real, but the impossible realized situation. The modal-temporal paradigm of the situation realization in complex sentences is fixed in the paradigm «indicative / imperative – subjunctive / infinitive». Key words: complex sentence, modality of volition, subjective volitional modality, objective propositional modality, voluntary / optative modus, propositional dictum, Early New English.